Superhydrophobic dyeing of orange fruit pigment on cotton knitted textile application - Marsi, Noraini; Tan, Ka Seng; Mohd Rus, Anika Zafiah; Mat Hassan, Nik Normunira (Penerbit UTHM, 2020)
The pigment is the substance that changes the colour of light based on the result of selective colour absorption. Pigments are used for colouring paint, fabric, ink, food, cosmetic and other materials. The materials that chosen and developed by human for use as pigment must have special properties that make them ideal for make them colouring other materials. The pigment must be stable in solid form at ambient temperatures [1]. Pigments can be divided into two groups which is organic pigment and inorganic pigment. For inorganic pigments, the colour is comparatively less bright and these pigments are also seemed to be less rich than the organic pigments. Large amount of inorganic pigments are required to generate desired effects since these pigments have low tinting strength. The most important thing is inorganic pigment contains toxic substances that may be harm to our health and environment. The researchers are started to investigate and use organic pigment into textile application nowadays [2].